Perspectivas y experiencias de violencias en las relaciones amorosas y/o eróticas en la juventud universitaria: un estudio en la FES Acatlán - García Solano, Leticia (2024)
To eradicate violence, it is essential to identify, make visible, and cease its reproduction—tasks that can undoubtedly be promoted within educational settings. The research conducted in universities represents one of the opportunities these institutions have to undertake actions that enable their communities to live in environments free from violence. This article is the result of one of the objectives of the research project “Diagnosis of Gender Violence at FES-Acatlán: Perceptions of the Mixed-Gender Student Community,” developed between 2023 and 2024, which aims to understand students’ perceptions of violence in dating and affective relationships. Among the findings, it is noteworthy that establishing erotic and/or affective relationships marked by violence during the university experience has various impacts; two of these are the distancing from friendships and a decline in academic performance.